DISCOURSE ANALYSIS OF ONLINE NEWS MEDIA ON SEXUAL VIOLENCE IN NORTH MALUKU - Syamsul Bahri Abd. Rasyid (Marwah: Jurnal Perempuan, Agama dan Jender, 2022)
This study aims to describe the phenomenon of sexual violence in North Maluku with discourse analysis, based on reports made by Tribunnews.com, Kompas.com, Kumparan.com, Malutpost.id, Halmaherapost.com, and Tandaseru.com, in 2020 and 2021. Qualitative-descriptive research was used in this study. The results showed that from the media chosen by the author, the media with the highest number of reports in the 2020-2021 period was Tandaseru.com. Meanwhile, on average, the intensity of reporting based on the type of sexual violence most frequently mentioned by the news media is rape. The relationship between the perpetrator and the victim also varies, ranging from close people, people who are known, actors who are in state institutions, to people (perpetrators) who are not known. In addition, the cluster analysis in NVivo 12 plus shows that each media has a relationship with a different level of relationship closeness value, which indicates that each media has produced narratives and opinions related to sexual violence in North Maluku.